Work as Meaningful and Menacing Phenomenon for South African Middle Managers During the COVID-19 Pandemic: The Role of Self-Transcendence in Cultivating Meaning and Wellbeing - Flotman, Aden-Paul (Frontiers in Psychology, 2021)
Self-transcendence has become and remains an important research theme. Little is known about the role of self-transcendence in cultivating meaningful work and its impact on the wellbeing of middle managers in the face of adversity, such as the Covid-19 pandemic. The aim of this qualitative hermeneutic phenomenological study was to explore the impact of the Covid-19 pandemic on the meaning middle managers attach to their work by investigating the role of self-transcendence in cultivating meaning and wellbeing in a cohort of seven South African middle managers employed in cross-boundary service industry settings. Data were collected through unstructured narratives. Findings confirm that self-transcendence serves as a coping mechanism during adversity and that it facilitates the re-negotiation of meaning, resulting in three potential shifts: the shift from a blame orientation to a work orientation, the shift from reflection to reflexivity and the shift from self-consciousness to other-consciousness. The findings also highlight how self-transcendence enables the exploration of the adaptive benefits of anxiety. The findings contribute new insights into the construct of self-transcendence and extend research on existential positive psychology. It is suggested that organizations invest in reflexive practices as a tool to promote deep learning and connectivity by exploring dialectical processes through reflexive work.